Bahasa Indonesia : Introduction to indonesian language and culture - Johns, Yohanni; Masinambow, E. K. M.; Haenen, Paul. (Jakarta : Periplus editions limited, 1990)
History and the use of Indonesian languange and vernacular languages based on the 1980 population census.
Includes bibliographical references (p. [116]-119) and indexes.
Pomi
Keywords: Indonesian language -- Usage; Indonesian language -- Dialects -- Indonesia -- History